Creative and successful set designs : how to make imaginative stage sets with limited Rresources - Muffatti, S. Todd (Atlantic Publishing Group, Inc., 2018)
"'Creative and Successful Set Designs' is a helpful resource for set designers, theater teachers, and performing arts directors to use to help avoid common pitfalls when creating the world of their production. Muffatti takes examples of sets from some of the best known works of drama and details the best ways to fully bring the set to life"--